Pengaruh Analisis Profitabilitas, Kebijakan Deviden dan Struktur Modal Terhadap Harga Saham (Sektor Properti dan Real Estate yang Terdaftar di BEI Periode Tahun 2016-2018) - Ulviyani, Geta (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2021)
The purpose of this research is to final out influence of profitability, dividend policy and capital structure to the stock price of property and real estate companies which are listed in Indonesia Stock Exchange. This research use secondary data in the animal report of property and real estate companies which are listed in Indonesia Stock Exchange in 2016 – 2018 periodes. This research is quantative type because in it refers to the calculation of resarch data in the form of numbers. The variabels of this study include dependent and independent variables. The sample was chosen using purposive sampling method, with the number of 15 companies during the periodes 2016 – 2018. Data analysis thechniquesuse are descriptive statistical test, classical assumption test, multiple linear regression analysis and hypothesis test. The analysis is done by using SPSS 23 program. The result of the reaserch show that profitability have an influence positive and significant effect toward stock price in property and real estate companies. Dividend policy have an influence negative and no significant toward dtock price in property and real estate companies, and capital structure have an influence positive and no significant effect toward stock price in property and real estate Keywords : stock price, profitability, dividend policy, capital structure.